Newsvendor Mergers - Cho, Soo-Haeng; Wang, Xin (Management Science, 2017)
This paper studies a merger between price-setting newsvendors in an oligopolistic market. It is well known that inventory pooling can greatly reduce inventory costs in a centralized distribution system because it helps reduce aggregate demand uncertainty. Although such statistical economies of scale are important benefits of a retail merger, the extant literature models cost savings from a merger only through reduction in a postmerger firm’s marginal cost. In this paper, we develop a model of a retail merger under uncertain demand that distinguishes between cost savings from conventional economies of scale and those from statistical economies of scale, and we show that these two sources of cost savings have substantially different impacts on firms’ decisions in a postmerger market. Contrary to the existing theory of mergers developed under deterministic demand, we find that although inventory pooling enables the postmerger firm to achieve cost savings, it always induces firms to raise their prices, and we find that marginal cost reduction induces firms to lower their prices only when it is substantial—consequently, larger cost synergies can benefit even nonparticipant firms. Finally, even if a merger induces all firms to raise their prices, it can still improve expected consumer welfare by increasing firms’ service levels under uncertain demand. This paper was accepted by Serguei Netessine, operations management.